Retrieval of Cu2+ and Cd2+ ions from aqueous solutions using sustainable guar gum/PVA/montmorillonite nanocomposite films: effect of temperature and adsorption isotherms - Alhaithloul, Haifa A. S.; Alsudays, Ibtisam Mohammed; Zaki, ElSayed G.; Elsaeed, Shymaa M.; Mubark, Amal E.; Salib, Lurana; Safwat, Gehan; Niedbała, Gniewko; Diab, Ayman; Abdein, Mohamed A.; Alharthi, Afaf; Zakai, Shadi A.; et al. (Frontiers in Chemistry, 2024)
Uncontrolled or improperly managed wastewater is considered toxic and dangerous to plants, animals, and people, as well as negatively impacting the ecosystem. In this research, the use of we aimed to prepare polymer nanocomposites (guar gum/polyvinyl alcohol, and nano-montmorillonite clay) for eliminating heavy metals from water-based systems, especially Cu2+ and Cd2+ ions. The synthesis of nanocomposites was done by the green method with different ratios of guar gum to PVA (50/50), (60/40), and (80/20) wt%, in addition to glycerol that acts as a cross-linker. Fourier-transform infrared spectroscopy (FT-IR) analysis of the prepared (guar gum/PVA/MMT) polymeric nano-composites’ structure and morphology revealed the presence of both guar gum and PVA’s functional groups in the polymeric network matrix. Transmission electron microscopy (TEM) analysis was also performed, which verified the creation of a nanocomposite. Furthermore, theromgravimetric analysis (TGA) demonstrated the biocomposites’ excellent thermal properties. For those metal ions, the extreme uptake was found at pH 6.0 in each instance. The Equilibrium uptake capacities of the three prepared nanocomposites were achieved within 240 min. The maximal capacities were found to be 95, 89 and 84 mg/g for Cu2+, and for Cd2+ were found to be 100, 91, 87 mg/g for guar gum (80/20, 60/40 and 50/50), respectively. The pseudo-2nd-order model with R2 > 0.98 was demonstrated to be followed by the adsorption reaction, according to the presented results. In less than 4 hours, the adsorption equilibrium was reached. Furthermore, a 1% EDTA solution could be used to revitalize the metal-ion-loaded nanocomposites for several cycles. The most promising nanocomposite with efficiency above 90% for the removal of Cu2+ and Cd2+ ions from wastewater was found to have a guar (80/20) weight percentage, according to the results obtained.